2017
DOI: 10.1186/s12913-017-2205-4
|View full text |Cite
|
Sign up to set email alerts
|

Personalized medicine in Europe: not yet personal enough?

Abstract: BackgroundPersonalized medicine has the potential to allow patients to receive drugs specific to their individual disease, and to increase the efficiency of the healthcare system. There is currently no comprehensive overview of personalized medicine, and this research aims to provide an overview of the concept and definition of personalized medicine in nine European countries.MethodsA targeted literature review of selected health databases and grey literature was conducted to collate information regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 48 publications
1
30
0
2
Order By: Relevance
“…On rst view, this result may be surprising because one might have supposed that their decision intuitively follows the 'real biochemical facts'. This is obviously too simplistic a view that reduces patients to their disease, as Di Paleo et al [30] suggested it in their review of personalized medicine; rather, the women seem to balance the invasive character of an antibiotic drug against the severity of symptoms.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On rst view, this result may be surprising because one might have supposed that their decision intuitively follows the 'real biochemical facts'. This is obviously too simplistic a view that reduces patients to their disease, as Di Paleo et al [30] suggested it in their review of personalized medicine; rather, the women seem to balance the invasive character of an antibiotic drug against the severity of symptoms.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Following the NICE [33] principles of medicines optimization, physicians could help women by discussing their preferences and what is important to them about managing their condition and their medicines and recognize and accept that the women's values and preferences may be different from their own. Doctors should understand that women's disease management will be affected by individual preferences for particular treatment modalities, the avoidance of certain side effects and a personal bene t-harm trade-off analysis of the available interventions and may differ in the level of priority they give to health and symptom recovery compared to other problems [30]. In the end, their decisions seem to have been wise because those who decided to take only NSAIDs fared nearly as well as those who took antibiotics.…”
Section: Implications For Practicementioning
confidence: 99%
“…31 However, internationally this role remains variable and a structured, appropriate and consistent approach is required. 3,[32][33][34] Within stratified medicine research, this issue is further compounded by all too frequent inconsistencies in nomenclature and misunderstanding of the concepts underpinning the field. Important partnerships and initiatives have started to address how individual patients and the public in general, understand and respond to the concept of stratified medicine.…”
Section: Stakeholders In Stratified Medicine the Patient And Researchermentioning
confidence: 99%
“…Stratified medicine, providing the right patient with the right drug at the right dose at the right time, is widely recognised to be of huge potential global benefit. 1,2,3 Also termed personalised or precision medicine, 3,4 stratification is undertaken to better direct therapy to gain a deeper understanding of the differing mechanisms of disease and treatment responses. Stratified medicine has become an important area of medical research across all clinical specialties, with far reaching impact in health economic, societal, political and industrial spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Health care spending is rapidly increasing in many countries, largely due to increasing pharmaceutical spending on new medications that are becoming available at very high prices to treat cancers and other chronic conditions of aging populations [1,2]. Highly-effective therapies that benefit large numbers of patients like the direct-acting antivirals for hepatitis C, rapidly-approved pharmaceuticals with uncertainty of effectiveness and safety like many new cancer therapies, and gene therapies for orphan diseases like spinal muscular atrophy that may benefit few require renewed discussions of the ethical dilemmas that arise around which treatments and services to cover, for whom, with how much patient cost-sharing, and at what opportunity costs to society [3]. Daniels and colleagues have argued that "resource allocation decisions in health care are rife with moral disagreement and a fair, deliberative process is necessary to establish the legitimacy and fairness of such decisions … the process must be public (fully transparent) about the grounds for its decisions; the decision must rest on reasons that stakeholders can agree are relevant; decisions should be revisable in light of new evidence and arguments; and there should be assurance through enforcement that these conditions are met."…”
Section: Introductionmentioning
confidence: 99%